2008
DOI: 10.1051/0004-6361:200810258
|View full text |Cite
|
Sign up to set email alerts
|

Non-LTE line formation for Pr ii  and Pr iii  in A and Ap stars

Abstract: Aims. Non-local thermodynamical equilibrium (non-LTE) line formation for singly-ionized and doubly-ionized praseodymium is considered for a range of effective temperatures between 7250 K and 9500 K. We evaluate the influence of departures from LTE on Pr abundance determinations and determine a distribution of the Pr abundance in the atmosphere of the roAp star HD 24 712 from a non-LTE analysis of the Pr ii and Pr iii lines. Methods. A comprehensive model atom for Pr ii/iii is presented based on the measured an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…As shown for Nd by Mashonkina et al (2005) and for Pr by Mashonkina et al (2009), the main non-LTE effect for their first ions in the model atmosphere representing the atmosphere of HD 24712 is overionization caused by a super-thermal radiation of non-local origin close to the thresholds of the lowexcitation levels. The departures from LTE for the lines of the first and the second ions are of the opposite sign and they are significant if the element is concentrated in the uppermost atmospheric layers where collisions are inefficient in establishing thermodynamic equilibrium.…”
Section: Nlte Calculationsmentioning
confidence: 84%
See 2 more Smart Citations
“…As shown for Nd by Mashonkina et al (2005) and for Pr by Mashonkina et al (2009), the main non-LTE effect for their first ions in the model atmosphere representing the atmosphere of HD 24712 is overionization caused by a super-thermal radiation of non-local origin close to the thresholds of the lowexcitation levels. The departures from LTE for the lines of the first and the second ions are of the opposite sign and they are significant if the element is concentrated in the uppermost atmospheric layers where collisions are inefficient in establishing thermodynamic equilibrium.…”
Section: Nlte Calculationsmentioning
confidence: 84%
“…For Pr and Nd, we performed a NLTE stratification analysis as described in Mashonkina et al (2009) and Mashonkina et al (2005) using a trial-and-error method and the observed equivalent widths of the lines of the first and second ions.…”
Section: Stratification Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that Mashonkina et al (2005Mashonkina et al ( , 2009) find important non-LTE effects in formation of lines of Pr and Nd ii and iii in magnetic Ap stars with T eff as low as 7250 K suggests that non-LTE effects in Si could potentially be important well below the conventional limit of T eff ≈ 15 000 K.…”
Section: Non-lte Effects In B-type Starsmentioning
confidence: 99%
“…For five species, Sr ii, Zr ii, Ba ii, Pr ii, and Eu ii, we performed NLTE calculations using the methods described in our earlier studies (Belyakova & Mashonkina 1997;Velichko et al 2010;Mashonkina et al 1999Mashonkina et al , 2009Mashonkina & Gehren 2000) and determined the NLTE element abundances. They are presented in Table 8 In contrast to Sr ii and Ba ii, the term structure of the other NLTE species is produced by multiple electronic configurations and consists of hundreds and thousands of energy levels.…”
Section: Nlte Effectsmentioning
confidence: 99%